A study of hybrid self-centring connections equipped with shape memory alloy washers and bolts. (1st June 2018) - Fang, Cheng; Yam, Michael C.H.; Chan, Tak-Ming; Wang, Wei; Yang, Xiao; Lin, Xuemei
Highlights: Innovative hybrid self-centring extended end-plate connections are proposed. The connections include SMA Belleville washers and SMA bolts. Experimental investigation on such connections is conducted. Numerical investigation and parametric study are conducted. A bi-linear design model is proposed for predicting the moment-rotation response. Abstract: This paper presents an innovative type of hybrid self-centring extended end-plate connections incorporating high strength bolts and two basic SMA elements, namely, SMA Belleville washers and SMA bolts. The fundamental mechanical characteristics of the individual SMA elements were first understood via cyclic tests, and subsequently a comprehensive test programme on of four proof-of-concept connections with varying bolt dimensions and washer arrangements was conducted. The connection specimens exhibited flag-shape hysteretic responses with good self-centring ability and cyclic loading repeatability. Satisfactory ductility accompanied by moderate energy dissipation capacity was also shown, and it was found that the SMA washers contributed evidently to the strength, stiffness, and energy dissipation of the connections. A numerical investigation was subsequently performed to enable a more in-depth understanding of the connection behaviour, and it was further shown that increasing the preload levels of either the SMA washers or the SMA bolts could effectively increase the connection stiffness. A design model was finally proposed which enables an idealised bi-linear description of the moment-rotation responses of the hybrid self-centring connections. The design stiffness and strength obtained from the proposed models were found to agree reasonably well with the test results and numerical predictions.